Análise dos conceitos teóricos empregados na clínica fonoaudiológica para aquisição da linguagem em surdos - Campello, Camilla Porto (2009)
This study addressed the speech therapy that is proposed for the acquisition of language in deaf children. The relevance of this study relates to the fact that in recent years criticisms being leveled against the participation of professional service and that there are few publications that depict the theoretical concepts and philosophies of education / rehabilitation used in speech therapy with these individuals . We know that depending on the choice theory that underlies the intervention, this service may or may not contribute to further development of the therapy. Once the purpose of this study was to analyze the theoretical concepts that are being employed in work with deaf speech, articulating with the philosophy of rehabilitation. For this we observe the consistency between theory and clinical practice, based on two case studies of children with bilateral deafness. Used as an instrument of data collection a semi-structured and as study material discursives therapies tape-K7. The interpretation of the data was based - in a thematic analysis. We see through the results of this research that the work of therapists, is based on current behavioral, which can be evidenced through the activities of repetition. The interactionist perspective marked in the interview of both therapists was not observed in clinical practice. The professionals worked only isolated concepts. They reported use in working with deaf the three philosophies of rehabilitation of these individuals: oral, total communication and bilingualism, but none was observed in therapy. We suggest that further investigations be carried out in order to deepen the knowledge about the theoretical concepts and philosophies of rehabilitation of the deaf in the speech clinic